Hadith #1140 - Sunan al-Nasa'i - al-Nu'man bin Rashid al-Jzry النعمان بن راشد الجزري أبو إسحاق الرقي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ata'a bin Yazid al-Laithi al-Junda'i عطاء بن يزيد الليثي الجندعي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ma'mar bin Rashid معمر بن راشد (Sunan al-Nasa'i)
“I used to bring to the Messenger of Allah (ﷺ) water for wudu and serve him. He said: ‘Ask of me.’ I said: ‘I want to be with you in Paradise.’ He said: ‘Is there anything else?’ I said: ‘That is all.’ He said: ‘Help me to fulfill your wish by prostrating a great deal.'”
Grade:

Hadith #2096 - Sunan al-Nasa'i - Aisha bint Abi Bakr; al-Nu'man bin Rashid al-Jzry النعمان بن راشد الجزري أبو إسحاق الرقي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Urwa ibn al-Zubayr عروة بن الزبير (Sunan al-Nasa'i)
“We were forbidden in the Quran to ask the Prophet about anything not imperative, so we liked it when a wise man from among the people of the desert came and asked him. A man from among the desert people came and said: ‘O Muhammad, your messenger came to us and told us that you say that Allah, the Mighty and Sublime, has sent you.’ He said: ‘He spoke the truth.’ He said: ‘Who created the heavens?’ He said: ‘Allah.’ He said: ‘Who created the Earth?’ He said: ‘Allah.’ He
Grade:

Hadith #5190 - Sunan al-Nasa'i - Abu Tha'laba al-Khushni; Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; al-Nu'man bin Rashid al-Jzry النعمان بن راشد الجزري أبو إسحاق الرقي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amr bin Mnswr al-Nsa'iy عمرو بن منصور النسائي أبو سعيد; Ata'a bin Yazid al-Laithi al-Junda'i عطاء بن يزيد الليثي الجندعي; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan al-Nasa'i)
The Messenger of Allah forbade (wearing) garments dyed with safflower, and Al-Qassiyah garments, and reciting Qur’an while he is bowing.
Grade: